2018
DOI: 10.1016/j.chempr.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Stereodivergent Synthesis of β,γ-Fused Bicyclic γ-Lactones via a Multicomponent Ring-Expansion Cascade

Abstract: The 3-alkoxy-1-N-toluenesulfonyl azopropene structural motif has been known in the context of the Eschenmoser-Tanabe fragmentation for over 50 years. It is derived from a-epoxy N-toluenesulfonyl hydrazones by deprotonation and epoxide ring opening. A very interesting yet unreported feature of these intermediates is their putative 1,3-dipolar nature and the potential to use them in reactions with complimentary dipoles to enable novel ring-expansion methods for the synthesis of saturated and partially saturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Carbon-carbon (C-C), carbonheteroatom (C-X), and heteroatom-heteroatom (X-Y) heterolytic fragmentation reactions offer methods for synthesizing structural motifs (some found in complex natural products) that might be difficult to synthesize using methods focused on bond formation. [1][2][3][4][5][6][7] Despite their continued use in organic synthesis [8][9][10][11][12][13][14][15][16][17] and their relevance to reactions occurring in mass spectrometers, 18 the application of heterolytic fragmentations in which multiple s-bonds are cleaved in synthetic campaigns is limited by putative strict conformational requirements (e.g., an anti-periplanar conformation for the bonds that cleave during fragmentation; Scheme 1). 4,19 Few theoretical and mechanistic studies [20][21][22][23][24] have provided insight into the physical underpinnings for this class of reaction since the seminal work of Grob.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-carbon (C-C), carbonheteroatom (C-X), and heteroatom-heteroatom (X-Y) heterolytic fragmentation reactions offer methods for synthesizing structural motifs (some found in complex natural products) that might be difficult to synthesize using methods focused on bond formation. [1][2][3][4][5][6][7] Despite their continued use in organic synthesis [8][9][10][11][12][13][14][15][16][17] and their relevance to reactions occurring in mass spectrometers, 18 the application of heterolytic fragmentations in which multiple s-bonds are cleaved in synthetic campaigns is limited by putative strict conformational requirements (e.g., an anti-periplanar conformation for the bonds that cleave during fragmentation; Scheme 1). 4,19 Few theoretical and mechanistic studies [20][21][22][23][24] have provided insight into the physical underpinnings for this class of reaction since the seminal work of Grob.…”
Section: Introductionmentioning
confidence: 99%
“…Stereodivergent synthesis 3750 has emerged as a powerful synthetic tool that allows access to stereoisomers of a product incorporating multiple stereogenic centers from the same set of substrates, which exactly caters for the ever-increasing drive in the pharmaceutical industry for molecular complexity in an effort to advance drug discovery and chemical-biology study 51–56 . Based on the utility of such strategy, we 57 and others 58 previously developed synergistic Cu/Ir catalyst systems for the stereodivergent access to α,α-disubstituted α-amino acids by the asymmetric allylation of aldimine esters with full control of the diastereoselectivity and enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrazones and their derivatives have received considerable attention as stable and versatile imine derivatives, , since their CN moieties behave as electrophiles of moderate reactivity with the availability of their chiral versions, e.g., (S)-1-amino-2-methoxymethylpyrrolidine (SAMP)/(R)-1-amino-2-methoxymethylpyrrolidine (RAMP) hydrazones and others . During our research into the α-iminoester, we have become interested in the reactivity of oxime derivatives as stable and useful substrates for the S N 2 type reaction at the nitrogen atom and for subsequent umpolung reactions to introduce plural substituents at the nitrogen (Scheme a). During the exploration into the S N 2 type reaction at the nitrogen atom, we focused on a relatively strong N–N bond of the hydrazone moiety and found that, once the N–N bond was cleaved, the cleaved nitrogen moiety behaved as a good nucleophile for the ester part to convert it to an amide.…”
mentioning
confidence: 99%